2006
DOI: 10.1002/mds.20887
|View full text |Cite
|
Sign up to set email alerts
|

Valvular heart disease in Parkinson's disease vs. controls: An echocardiographic study

Abstract: Restrictive valvulopathy has been reported in association with dopamine agonist therapy in parkinsonian patients. The majority of reports have been related to pergolide, but anecdotal cases following treatment with bromocriptine or cabergoline have also been presented. It is presently unclear whether the potential induction of restrictive cardiac valvulopathy is a class effect of all dopamine agonists or if there is a differential risk between ergot and nonergot compounds. In this study, the frequency of a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 17 publications
5
53
1
3
Order By: Relevance
“…Moreover composite regurgitation score was higher in patients using cabergoline which was associated both with duration and cumulative dose of cabergoline therapy as in line with previous studies (15,18). In addition to valvular regurgitation, morphologic features including leaflet and subvalvular apparatus thickening were more prevalent in patient using cabergoline similar to previous studies (19).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover composite regurgitation score was higher in patients using cabergoline which was associated both with duration and cumulative dose of cabergoline therapy as in line with previous studies (15,18). In addition to valvular regurgitation, morphologic features including leaflet and subvalvular apparatus thickening were more prevalent in patient using cabergoline similar to previous studies (19).…”
Section: Discussionsupporting
confidence: 89%
“…■ Key words Parkinson's disease · pergolide · valvular heart disease · echocardiography 9] have focused on the more specific restrictive valvulopathy and reported frequencies of 33 % [1], 3 % [7], and 0 % [9], respectively. No study has systematically examined the course of valvulopathy following pergolide discontinuation.…”
mentioning
confidence: 99%
“…Several echocardiographic prevalence studies reported increased risk of valvular heart disease (VHD) in patients taking ergot DAs (cabergoline, pergolide) compared to non-ergot DAs (pramipexole, ropinirole) [7][8][9] and an association between cumulative dose and severity of valve regurgitation [9]. A systematic review confirmed these findings assessing an increased risk of cardiac valve regurgitation associated with the use of ergot DAs and not of non-ergot DAs [10].…”
Section: Introductionmentioning
confidence: 89%